Textured Building Façades: Utilizing Morphological Adaptations Found in Nature for Evaporative Cooling - Megan Peeks; Lidia Badarnah (Biomimetics, 2021)
The overheating of buildings and their need for mechanical cooling is a growing issue as a result of climate change. The main aim of this paper is to examine the impact of surface texture on heat loss capabilities of concrete panels through evaporative cooling. Organisms maintain their body temperature in very narrow ranges in order to survive, where they employ morphological and behavioral means to complement physiological strategies for adaptation. This research follows a biomimetic approach to develop a design solution. The skin morphology of elephants was identified as a successful example that utilizes evaporative cooling and has, therefore, informed the realization of a textured façade panel. A systematic process has been undertaken to examine the impact of different variables on the cooling ability of the panels, bringing in new morphological considerations for surface texture. The results showed that the morphological variables of assembly and depth of texture have impact on heat loss, and the impact of surface area to volume (SA:V) ratios on heat loss capabilities varies for different surface roughness. This study demonstrates the potential exploitation of morphological adaptation to buildings, that could contribute to them cooling passively and reduce the need for expensive and energy consuming mechanical systems. Furthermore, it suggests areas for further investigation and opens new avenues for novel thermal solutions inspired by nature for the built environment.